Peran Ilmu Al-Ashwat dalam Pelafalan Huruf Hijaiyah (KajianTeoritik Linguistik Terapan) - Muhammad Nur Sholihin (STAI Terpadu Yogyakarta, 2020)
Shaut or sound is one of the basics of all languages ​​on this earth, whose involvement determines the validity and reliability of the language itself and supports it to continue to exist. Departing from the importance of the position of sound or shaut, in the realm of lughat was born the AL-ASHWAT SCIENCE, which subsequently in linguistics was called phonology. The role of ashwat science is certainly inevitable, so the research that the author is doing this time aims to reveal how important understanding of al-ashwat science theory is and where its weak point is at the level of applied pronunciation of hijaiyah letters. This type of research is library research or literature review. While the data collection method uses the documentation method. The data analysis that the author does is editing, organizing and inference. The results of his research are an understanding of ashwat in more depth and mistakes that often occur more clearly. Even when someone enters a practical level in the domain of Tajweed, without the correct understanding of shifatul letters it is impossible to realize the right and correct makharijul letters. Thus in the process of talaqqi, the expert tutor should be present in the learning of reading hijaiyah letters, the language of the Qur'an and so on.